ALUR GERAKAN PEMAKAIAN KONTRASEPSI DI JAWA TENGAH (ANALISIS DATA SUSENAS 2017) - El Rohim, Nur Hafidhah (Universitas Tribhuwana Tunggadewi, 2019)
Data on users of contraceptive methods are needed to evaluate contraceptive use and plan for future needs. Changes in contraceptive methods and factors that influence the use of certain contraceptive methods are serious things to consider. The purpose of this study was to look at the dynamics and transition path of contraceptive use in Central Java. 2017 National Socio-Economic Survey (Susenas) data, especially contraceptive use for couples of childbearing age (PUS) aged 15-49 years is a reference. The statistical method applied in this study is descriptive analysis and inferential test. The results of the analysis show a shift and transition from modern methods to traditional methods. The study also found a positive relationship between the choice of contraceptive methods used and EFA residence. There is a positive relationship between the variables of first marriage age, education and EFA residence to the change in contraceptive method. Keywords : KB; Purbalingga; Susenas; Temanggung.